Gelam honey scavenges peroxynitrite during the immune response - Kassim, M.; Mansor, M.; Suhaimi, A.; Ong, G.; Yusoff, K.M. (2012)
Monocytes and macrophages are part of the first-line defense against bacterial, fungal, and viral infections during host immune responses; they express high levels of proinflammatory cytokines and cytotoxic molecules, including nitric oxide, reactive oxygen species, and their reaction product peroxynitrite. Peroxynitrite is a short-lived oxidant and a potent inducer of cell death. Honey, in addition to its well-known sweetening properties, is a natural antioxidant that has been used since ancient times in traditional medicine. We examined the ability of Gelam honey, derived from the Gelam tree (Melaleuca spp.), to scavenge peroxynitrite during immune responses mounted in the murine macrophage cell line RAW 264.7 when stimulated with lipopolysaccharide/interferon-Î³ (LPS/IFN-Î³) and in LPS-treated rats. Gelam honey significantly improved the viability of LPS/IFN-Î³-treated RAW 264.7 cells and inhibited nitric oxide production-similar to the effects observed with an inhibitor of inducible nitric oxide synthase (1400W). Furthermore, honey, but not 1400W, inhibited peroxynitrite production from the synthetic substrate 3-morpholinosydnonimine (SIN-1) and prevented the peroxynitrite-mediated conversion of dihydrorhodamine 123 to its fluorescent oxidation product rhodamine 123. Honey inhibited peroxynitrite synthesis in LPS-treated rats. Thus, honey may attenuate inflammatory responses that lead to cell damage and death, suggesting its therapeutic uses for several inflammatory disorders. Â© 2012 by the authors; licensee MDPI, Basel, Switzerland.